Impact of Vaccination Status on Outcome of Patients With COVID-19 and Acute Ischemic Stroke Undergoing Mechanical Thrombectomy - Deuschl, Cornelius; Goertz, Lukas; Kabbasch, Christoph; Köhrmann, Martin; Kleinschnitz, Christoph; Berlis, Ansgar; Maurer, Christoph Johannes; Mühlen, Iris; Kallmünzer, Bernd; Gawlitza, Matthias; Kaiser, Daniel P.O.; Klisch, Joachim; et al. (Journal of the American Heart Association, 2024)
BACKGROUND: Data on impact of COVID-19 vaccination and outcomes of patients with COVID-19 and acute ischemic stroke undergoing mechanical thrombectomy are scarce. Addressing this subject, we report our multicenter experience. METHODS AND RESULTS: This was a retrospective analysis of patients with COVID-19 and known vaccination status treated with mechanical thrombectomy for acute ischemic stroke at 20 tertiary care centers between January 2020 and January 2023. Baseline demographics, angiographic outcome, and clinical outcome evaluated by the modified Rankin Scale score at discharge were noted. A multivariate analysis was conducted to test whether these variables were associated with an unfavorable outcome, defined as modified Rankin Scale score >3. A total of 137 patients with acute ischemic stroke (48 vaccinated and 89 unvaccinated) with acute or subsided COVID-19 infection who underwent mechanical thrombectomy attributable to vessel occlusion were included in the study. Angiographic outcomes between vaccinated and unvaccinated patients were similar (modified Thrombolysis in Cerebral Infarction ≥2b: 85.4% in vaccinated patients versus 86.5% in unvaccinated patients; P=0.859). The rate of functional independence (modified Rankin Scale score, ≤2) was 23.3% in the vaccinated group and 20.9% in the unvaccinated group (P=0.763). The mortality rate was 30% in both groups. In the multivariable analysis, vaccination status was not a significant predictor for an unfavorable outcome (P=0.957). However, acute COVID-19 infection remained significant (odds ratio, 1.197 [95% CI, 1.007-1.417]; P=0.041). CONCLUSIONS: Our study demonstrated no impact of COVID-19 vaccination on angiographic or clinical outcome of COVID-19-positive patients with acute ischemic stroke undergoing mechanical thrombectomy, whereas worsening attributable to COVID-19 was confirmed.
CRIS-Team Scopus Importer:2024-05-17
Keywords: acute ischemic stroke; COVID‐19; COVID‐19 vaccination; mechanical thrombectomy